ETIKA PENGGUNAAN GADGET DALAM MENINGKATKAN KESADARAN SISWA TERHADAP PENGGUNAAN TEKNOLOGI YANG BIJAK DI MTsN 1 LAMPUNG UTARA - muinah muinah; Jingga Ameira; Farenisa Azahra; Erdy Arista Desti; Nanda Putri; Sigit Gunanto; Fhela Vhantoria Ningrum (Sentra Kekayaan Intelektual dan Publikasi Ilmiah, 2026)
This community service activity aimed to improve students’ understanding of ethical gadget use in the digital era and encourage responsible and productive technology management. The activity was conducted in the form of an educational seminar at MTsN 1 Lampung Utara using interactive lectures and participatory discussions. The program involved 50 students from the Organisasi Siswa Intra Madrasah (OSIM). The results indicated that students gained a better understanding of both the positive and negative impacts of gadget use. Gadgets were recognized as effective tools for learning, communication, and creativity development when used appropriately. However, excessive and uncontrolled use may lead to digital addiction, decreased academic focus, physical health problems, and reduced social interaction. The seminar also strengthened students’ awareness of digital ethics and self-control in managing screen time. Overall, the activity successfully addressed the identified problems and contributed to strengthening students’ digital character in the school environment.